Modeling Spitz melanoma in zebrafish using sequential mutagenesis - Jeffrey K. Mito; Margaret C. Weber; Alexandra Corbin; George F. Murphy; Leonard I. Zon (The Company of Biologists, 2022)
Spitz neoplasms are a diverse group of molecularly and histologically defined melanocytic tumors with varying biologic potentials. The precise classification of Spitz neoplasms can be challenging. Recent studies have revealed recurrent fusions involving multiple kinases in a large proportion of Spitz tumors. In this study, we generated a transgenic zebrafish model of Spitz melanoma using a previously identified ZCCHC8-ROS1 fusion gene. Animals developed grossly apparent melanocytic proliferations as early as 3 weeks of age and overt melanoma as early as 5 weeks. By 7 weeks, ZCCHC8-ROS1 induced a histologic spectrum of neoplasms ranging from hyperpigmented patches to melanoma. Given the swift onset of these tumors during development, we extended this approach into adult fish using a recently described electroporation technique. Tissue-specific expression of ZCCHC8-ROS1 in adults led to melanocyte expansion without overt progression to melanoma. Subsequent electroporation with tissue-specific CRISPR, targeting only tp53 was sufficient to induce transformation to melanoma. Our model exhibits the use of sequential mutagenesis in the adult zebrafish, and demonstrates that ZCCHC8-ROS1 induces a spectrum of melanocytic lesions that closely mimics human Spitz neoplasms.